DI BALIK SENYAP KONFLIK: RESILIENSI PSIKOLOGIS PRAJURIT TNI DI PAPUA - Febrio Xavier, Selyo; Pasca Rini, Rr. Amanda; Suryanto, Suryanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Military assignments in conflict areas such as Papua expose Indonesian Army (TNI) soldiers to physical threats and psychological pressures that can impair psychological functioning and mission readiness. Resilience, as the ability to endure and adapt in extreme conditions, is crucial in this context. This study aims to analyze the dynamics of resilience among TNI soldiers in Papua, focusing on risk factors, protective mechanisms, and psychological processes that support their endurance and performance in the field. A qualitative approach with in-depth interviews and thematic analysis was used to explore the soldiers' subjective experiences in managing stress, using coping strategies, and deriving meaning from their deployment experiences in conflict areas. The findings indicate that resilience develops through the interaction of emotional regulation, flexible coping strategies, strong social support, and spirituality as a key psychological resource. The deployment also contributes to the positive transformation of soldiers, including enhanced emotional maturity and prosocial orientation. This study provides practical insights for the TNI in designing training programs and psychological support based on spirituality and social support to enhance the mental readiness of soldiers in conflict areas. ABSTRAK Penugasan militer di daerah konflik seperti Papua menempatkan prajurit TNI pada ancaman fisik dan tekanan psikologis yang dapat mengganggu fungsi psikologis dan kesiapan tugas. Resiliensi, sebagai kemampuan untuk bertahan dan beradaptasi dalam kondisi ekstrem, sangat penting dalam konteks ini. Penelitian ini bertujuan untuk menganalisis dinamika resiliensi prajurit TNI di Papua, dengan fokus pada faktor risiko, mekanisme protektif, dan proses psikologis yang mendukung ketahanan dan kinerja mereka di lapangan. Pendekatan kualitatif dengan wawancara mendalam dan analisis tematik digunakan untuk menggali pengalaman subjektif prajurit dalam mengelola stres, menggunakan strategi coping, dan membangun makna dari pengalaman penugasan di daerah konflik.Temuan menunjukkan bahwa resiliensi berkembang melalui interaksi antara regulasi emosi, penggunaan strategi coping yang fleksibel, dukungan sosial yang kuat, dan spiritualitas sebagai sumber daya psikologis utama. Penugasan ini juga berkontribusi pada transformasi positif prajurit, termasuk peningkatan kedewasaan emosional dan orientasi prososial. Penelitian ini memberikan wawasan praktis bagi TNI dalam merancang program pelatihan dan dukungan psikologis berbasis spiritualitas dan dukungan sosial untuk meningkatkan kesiapan mental prajurit di daerah konflik.